Carbon Starved Anther modulates sugar and ABA metabolism to protect rice seed germination and seedling fitness. Issue 4 (13th August 2021) - Sun, Linlin; Yuan, Zheng; Wang, Duoxiang; Li, Jingbin; Shi, Jin; Hu, Yangyang; Yu, Jing; Chen, Xiaofei; Chen, Sixue; Liang, Wanqi; Zhang, Dabing
Abstract: Seed germination is critical for plant survival and agricultural production, which is affected by both internal seed factors and external environmental conditions. However, the genetic basis and underlying molecular mechanisms of early seed germination in crops remain largely unclear. Here, we report that R2R3 MYB transcription factor Carbon Starved Anther ( CSA ) is expressed specifically in Oryza sativa embryo and aleurone in response to seed imbibition, peaking at 3–6 h and undetectable by 24-h post-imbibition. CSA seeds germinated more quickly than wild-type rice seeds and had higher levels of amylase activity, glucose, and inactive abscisic acid-glucose ester (ABA-GE), but lower levels of ABA. Through analyzing the CSA -associated transcriptome and CSA binding to downstream target genes, we identified two glycolytic genes as direct CSA targets. CSA inhibits Amylase 3A expression to limit glucose production from starch and activates Os3BGlu6 expression to promote de-conjugation of ABA-GE to ABA; these functions serve to slow germination and improve seedling resilience to abiotic stress in the first 3 weeks of growth. Therefore, this study unveils a protection mechanism conferred by CSA during early seed germination by balancing glucose and ABA metabolism to optimize seed germination and stress response fitness. Abstract : Carbon Starved Anther acts via a previously unrecognized protection mechanism during early seed germination by balancing glucose and ABA homeostasis to optimize seed germination processes and stress response fitness.